2018
DOI: 10.4172/2329-9029.1000204
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450s: Blueprints for Potential Applications in Plants

Abstract: Cytochrome P450s belong to a particular class of enzymes (Oxygenases) which are extensively distributed in all classes of organisms that attract the interest of scientists worldwide. It has been proved multi-functioned super gene family that sophisticates the biosynthesis of several endogenous molecules and metabolism of discrete pharmacologically important oxymolecules such as Antibiotics, essential secondary metabolites, fatty acid conjugates, signaling molecules, lipid degradation, hormones and many more. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The SNP markers associated with the linkage blocks M1.37719614 (qGYP1.2), M12.4534450 (qHGW12.1), M1.38398157 (qPH1), M4.28368337 (qPH4), and M7.25991230 (qPH7) would be indicated for the development and validation of (Naveed et al, 2018). The SNP marker M2.34471005 (qPH2) is located between the genes LOC_Os02g56310 (phosphoenolpyruvate carboxylase kinase 2) and LOC_Os02g56320 (starch synthase 4).…”
Section: Resultsmentioning
confidence: 99%
“…The SNP markers associated with the linkage blocks M1.37719614 (qGYP1.2), M12.4534450 (qHGW12.1), M1.38398157 (qPH1), M4.28368337 (qPH4), and M7.25991230 (qPH7) would be indicated for the development and validation of (Naveed et al, 2018). The SNP marker M2.34471005 (qPH2) is located between the genes LOC_Os02g56310 (phosphoenolpyruvate carboxylase kinase 2) and LOC_Os02g56320 (starch synthase 4).…”
Section: Resultsmentioning
confidence: 99%
“…The CYPs and UGTs, which are a specific class of oxidoreductases and transferases, have been proven to be multifunctional candidates that regulate the biosynthesis and diversification of secondary metabolites [ 29 , 30 ]. In total, 602 transcripts encoding 44 CYP families were identified in A. glauca , with abundances of CYP71, CYP72, CYP76, CYP704, and CYP81.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the expression of CYP in blue-light-irradiated L. edodes increases with fruiting body development and shows consistently high expression at all growth stages [ 13 ]. The role of CYPs in pigment biosynthesis in plants is well known [ 53 , 54 , 55 ], but the relationship between CYPs and fruiting body color in basidiomycetes is still unclear. The biological clock controls many metabolic processes in various organisms, including microorganisms, plants, and animals.…”
Section: Discussionmentioning
confidence: 99%